2022
DOI: 10.1126/sciadv.abm7201
|View full text |Cite
|
Sign up to set email alerts
|

Investigating trends in those who experience menstrual bleeding changes after SARS-CoV-2 vaccination

Abstract: Early in 2021, many people began sharing that they experienced unexpected menstrual bleeding after SARS-CoV-2 inoculation. We investigated this emerging phenomenon of changed menstrual bleeding patterns among a convenience sample of currently and formerly menstruating people using a web-based survey. In this sample, 42% of people with regular menstrual cycles bled more heavily than usual, while 44% reported no change after being vaccinated. Among respondents who typically do not menstruate, 71% of people on lo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
91
3
20

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(126 citation statements)
references
References 79 publications
12
91
3
20
Order By: Relevance
“…The majority of them were suffering from heavy bleeding (24.64%) followed by menstruation frequency longer than 35 days (23.19%), painful bleeding (19.32%), menstruation frequency shorter than 25 days (16.9%) and light bleeding for fewer periods (15.94%). In a Similar study Lee et al (6) have reported that 56% of the women who took Covid-19 vaccination were having menstrual irregularities. In this study 42.1% of the total respondent reported heavier menstrual flow while 14.3% reported not heavier menstrual flow (characterized by a mix or higher or no change).…”
Section: Discussionmentioning
confidence: 82%
“…The majority of them were suffering from heavy bleeding (24.64%) followed by menstruation frequency longer than 35 days (23.19%), painful bleeding (19.32%), menstruation frequency shorter than 25 days (16.9%) and light bleeding for fewer periods (15.94%). In a Similar study Lee et al (6) have reported that 56% of the women who took Covid-19 vaccination were having menstrual irregularities. In this study 42.1% of the total respondent reported heavier menstrual flow while 14.3% reported not heavier menstrual flow (characterized by a mix or higher or no change).…”
Section: Discussionmentioning
confidence: 82%
“…It remains an understudied topic; since the beginning of the immunization program for COVID-19, quite a significant fraction of people have reported experiencing sudden changes in their menstrual bleeding patterns. Individuals and groups that were hesitant to get vaccinated and anti-vaccine activists associated the risk of short-term menstrual interruptions with long-term reproductive issues [ 29 ]. Therefore, similar studies need to be conducted to clear such misconceptions and ensure that the vaccine is causing no harmful effects.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the incidence and the possible pathophysiology of the adverse events related to vaccination, a great number of studies have been published [226][227][228][229][230][231][232][233] although still a clear-cut evidence about their incidence and pathomechanisms does not exist.…”
Section: Discussionmentioning
confidence: 99%